Role of Desire and Implementation of Intention in the Theory of Planned Behavior: A Bibliometric Analysis - Uturestantix Uturestantix; Bernardinus Maria Purwanto; Andy Susilo Lukito-Budi (Binus Business Review, 2022)
A weak finding of behavioral intention and behavior in the Theory of Planned Behavior (TPB) from a meta-analysis study by Armitage and Conner in 2001 has led to an increasing number of studies aiming to improve the TPB. Several researchers propose potential constructs to bridge the theoretical and empirical gap by suggesting that the construct of desire and the implementation of intentions can fill the theoretical and empirical gaps in the TPB model. The literature study aimed to retrospectively explore TPB studies with desire and implementation of intentions constructs in the behavioral science domain. The research retrieved 191 SCOPUS indexed papers (2012–2019) from the Google Scholars database. It summarized the descriptive data and produced visualization using VOSviewer. The results show that most studies developing the TPB model with other behavioral theories still focus on constructs to shape behavioral intentions because the behavioral intention construct is the best predictor of behavior. Most studies apply a quantitative approach with a cross-sectional survey design to collect primary data. In contrast, the experimental and longitudinal design approaches are relatively neglected in this TPB behavioral study. Furthermore, the analysis of 191 papers shows that the TPB model is often used in research in environmental, sustainable, and transport settings; health; psychological; hospitality and tourism; and innovation and technology. In addition, the use of the TPB model in research with entrepreneurial and legal settings is still limited. From these findings, the research proposes empirical research on TPB to implement further the relationship between desire and intention implementation to improve the TPB model by integrating the TPB model with several other theories, such as Mindset Theory of Action Phase and Model Goal-Directed Behaviour.